2021
DOI: 10.3389/fphar.2021.667644
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavones of Abelmoschus manihot Ameliorates Podocyte Pyroptosis and Injury in High Glucose Conditions by Targeting METTL3-Dependent m6A Modification-Mediated NLRP3-Inflammasome Activation and PTEN/PI3K/Akt Signaling

Abstract: Background: The total flavones of Abelmoschus manihot (TFA), a compound that is extracted from Abelmoschus manihot, has been widely used in China to reduce podocyte injury in diabetic kidney disease (DKD). However, the mechanisms underlying the therapeutic action of this compound have yet to be elucidated. Podocyte pyroptosis is characterized by activation of the NLRP3 inflammasome and plays an important role in inflammation-mediated diabetic kidneys. Regulation of the PTEN/PI3K/Akt pathway is an effective str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…These data suggest that METTL14 and WTAP may play an important role in renal glomerulus and tubules, respectively. Moreover, the extensive m 6 A modification of NLRP3 mRNA by METTL3 in HG-afflicted podocytes has also been confirmed [ 54 ]. METTL14 also increased the m 6 A modification of NLRP3 mRNA in degenerative nucleus pulposus cells, while the reader decoding the m 6 A modification was different [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that METTL14 and WTAP may play an important role in renal glomerulus and tubules, respectively. Moreover, the extensive m 6 A modification of NLRP3 mRNA by METTL3 in HG-afflicted podocytes has also been confirmed [ 54 ]. METTL14 also increased the m 6 A modification of NLRP3 mRNA in degenerative nucleus pulposus cells, while the reader decoding the m 6 A modification was different [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is a cell death pathway that is characterized by the activation of various caspases including caspase-1 which is mediated by inflammasomes and causes cell perforation ( Mulay, 2019 ). Studies have suggested that m 6 A plays a key role in the regulatory pathway responsible for pyroptosis in cells ( Zha et al, 2020 ; Liu et al, 2021 ). NOD-like receptor protein 3 (NLRP3) is a key component of the inflammasome that causes pyroptosis and is known to promote pyroptosis and increase the levels of pro-inflammatory cytokines ( Mulay, 2019 ).…”
Section: The Role Of M 6 a In Pcdmentioning
confidence: 99%
“…The knockdown of WTAP inhibited pyroptosis and diminished the release of IL-18, IL-1b, caspase-1, and NLRP3 in high-glucoseinduced HK-2 cells (33). In clinical applications of regulators targeting RNA modification enzymes, a cell experiment demonstrated the total flavones of Abelmoschus Manihot, the main components of the Huangkui capsule and ameliorated pyroptosis and injury in podocytes under high-glucose conditions by adjusting METTL3-dependent m 6 A modification and regulating NLRP3-inflammasome activation and PTEN/PK13/Akt signaling (50).…”
Section: Function and Mechanism Of M 6 A And Methylesterase In Dnmentioning
confidence: 99%